Lifelong education and learning, societal project and competitive advantage: tensions and ambivalences in policy and planning of educational change in Portugal - Antunes, Fátima (2014)
Both the Portuguese appropriation of the lifelong learning policy proposed by the European Union since the mid-1990s and the definition of adult education policy in Portugal were based on a discourse that emphasised an ‘unacceptable educational deficit’ for democracy. The role of the State in the governance of the public provision of adult education was linked to its disengagement or precarious contractual involvement in the same. In this article, we discuss developments in adult education and training policy from the mid-1990s to 2010 in terms of an ambivalent policy dynamic and orientation of educational change, examining how a civil society organisation used adult education as a tool for rural development, to support the economy and individual resilience in the face of socio-economic weaknesses and risks.